2013
DOI: 10.1016/j.bpj.2013.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Phospholamban Stabilizes a Compact Conformation of the Cardiac Calcium-ATPase

Abstract: The sarcoendoplasmic reticulum calcium ATPase (SERCA) plays a key role in cardiac calcium handling and is considered a high-value target for the treatment of heart failure. SERCA undergoes conformational changes as it harnesses the chemical energy of ATP for active transport. X-ray crystallography has provided insight into SERCA structural substates, but it is not known how well these static snapshots describe in vivo conformational dynamics. The goals of this work were to quantify the direction and magnitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
59
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 55 publications
12
59
0
Order By: Relevance
“…1C) as observed previously for fluorescently labeled wild-type (WT)-PLB (32). The fluorescence pattern is consistent with localization in the sarcoplasmic reticulum and is similar to that previously observed for fluorescently labeled SERCA2a (32,37). R9C mutation is within the epitope region for the PLB-2D12 antibody (between amino acid residues 9 and 17 of canine PLB), and we observed that this mutation abolishes 2D12 reactivity (Fig.…”
Section: R9c-plb Exerts a Positive Inotropic And Positive Lusitropicsupporting
confidence: 74%
See 1 more Smart Citation
“…1C) as observed previously for fluorescently labeled wild-type (WT)-PLB (32). The fluorescence pattern is consistent with localization in the sarcoplasmic reticulum and is similar to that previously observed for fluorescently labeled SERCA2a (32,37). R9C mutation is within the epitope region for the PLB-2D12 antibody (between amino acid residues 9 and 17 of canine PLB), and we observed that this mutation abolishes 2D12 reactivity (Fig.…”
Section: R9c-plb Exerts a Positive Inotropic And Positive Lusitropicsupporting
confidence: 74%
“…Cardiomyocytes were incubated at 37°C for 1 h, and CFP-PLB and/or YFP-PLB adenoviruses were added at a multiplicity of infection of 1000 as described previously (37). Cardiomyocytes were then paced for 48 h in culture using a C-Pace EP Pacer (IonOptix, Milton, MA) set to 10 V with a frequency of 0.1 Hz, with 5-ms pulse duration (32,37).…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the putative misregistration of the PLB TM domain in the SERCA regulatory cleft may result in a noninhibitory interaction. We and others have previously provided evidence that PLB and SERCA can interact in a noninhibitory complex in the presence of Ca 2ϩ (29,62,63) or after PLB phosphorylation (64). This physiological relief of inhibition also alters the affinity and structure of the PLB-SERCA complex (29,(62)(63)(64).…”
Section: Discussionmentioning
confidence: 88%
“…AMP-PCP, adenylylmethylenediphosphonate. et al, 2012;Pallikkuth et al, 2013). Moreover, substrate binding may not induce an all-or-nothing switch to a new conformation but rather shift the balance of an equilibrium of multiple structures.…”
Section: Mrp1 Conformational Changesmentioning
confidence: 99%
“…Specifically, a conformational change that brings the nucleotidebinding domains closer together was expected to increase FRET from a basal level to a new higher level, reflecting the closer proximity of the fluorescent tags. We have previously used this approach to monitor structural dynamics of a calcium transporter within the native environment of the cell membrane (Hou et al, 2012;Pallikkuth et al, 2013). This strategy may be of general utility for investigating the conformational changes of transporter proteins in the native environment of the live cell.…”
Section: Introductionmentioning
confidence: 99%